Tubular dysfunction in type I diabetes mellitus. Issue 10 (October 1985) - Miltényi, M; Körner, A; Tulassay, T; Szabó, A
Abstract : Tubular function was investigated in patients with diabetic ketoacidosis and those with poorly controlled type I diabetes. Urinary excretion of beta 2 microglobulin and that of certain enzymes: gamma glutamyltransferase, leucine aminopeptidase, and N-acetyl-beta-D-glucosaminidase activities were significantly raised during ketoacidosis in 11 patients compared with healthy controls. In 13 poorly controlled diabetics, tubular electrolyte transport was studied and a significant reduction in tubular phosphate and sodium reabsorption was found. Tubular dysfunction occurring during diabetic ketoacidosis and in poorly controlled diabetics may contribute to the development of diabetic nephropathy.